Transformasi pembelajaran abad 21: menggali praktik baik implementasi P5 dalam kurikulum merdeka di sekolah dasar - Prapti, Suprapti; Wiyati, Indar; Yuliana, Erma; Kanzunidin, Muh; Rondli, Wawan Shokib (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
Abstract The research aims to explore good practices of P5 in the Merdeka Curriculum in elementary schools related to the development of 21st century skills. The research uses a qualitative method with a case study design involving two elementary schools, namely SD Negeri 4 Suru and SD Negeri 3 Gundih. Data were collected through observation, interviews, and document analysis. The results showed that both schools have successfully implemented P5 by integrating 21st century skills, such as digital literacy and critical thinking. Supporting factors for the successful implementation of P5 include principal support, collaboration among teachers, availability of resources, and active involvement of students and parents. However, there are also some inhibiting factors, such as teachers' lack of understanding of P5 concepts and objectives, time constraints and high teacher workloads. This study provides empirical evidence on the potential of P5 in developing 21st century skills and student character in primary schools, and provides recommendations for schools and stakeholders to improve the quality of P5 implementation. Keywords: self-contained curriculum; 21st century learning; P5; primary school